1992
DOI: 10.1111/j.1365-2621.1992.tb06845.x
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Aggregation Properties of Duck Salt‐Soluble Proteins at Selected pH Values

Abstract: Thermal aggregation p?operties of duck breast and leg salt-soluble proteins (SSP) were studied at pH 5.50, 5.75 and 6.00. At pH 5.50, a major iran&ion for breast was observed at 60.3"C and for leg at 41.8'C. At OH 5.75. maior transitions at 44.6 and 43.2"C were obtained, resp&tiveli,'for ihe breast and leg SSP. Three transitions at 46.0, 53.0 and 59.O"C were exhibited by breast SSP at pH 6.00, whereas only two major transitions at 47.4 and 54.O"C were identified in leg SSP. Changes in transition peak heights a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

1994
1994
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 29 publications
2
5
0
Order By: Relevance
“…Other physicochemical changes or processes, e.g., aggregation, seem to play a more direct and pivotal role in protein gelation. Indeed, the pronounced differences existed between poultry white and red myosin and SSP in thermal aggregation patterns (Liu and Foegeding, 1996a;Ndi and Brekke, 1992;Xiong and Brekke, 1990a;Xiong, 1992), did seem to confirm that rheological variations between white and red myosin and SSP gels are probably confined to this stage of gelation.…”
Section: Protein Denaturationsupporting
confidence: 51%
See 2 more Smart Citations
“…Other physicochemical changes or processes, e.g., aggregation, seem to play a more direct and pivotal role in protein gelation. Indeed, the pronounced differences existed between poultry white and red myosin and SSP in thermal aggregation patterns (Liu and Foegeding, 1996a;Ndi and Brekke, 1992;Xiong and Brekke, 1990a;Xiong, 1992), did seem to confirm that rheological variations between white and red myosin and SSP gels are probably confined to this stage of gelation.…”
Section: Protein Denaturationsupporting
confidence: 51%
“…Duck breast SSP (0.3 mg/ml) at pH 5.5, 5.75 and 6.0, when heated at 1 C/min from 20 to 70 C, produced one, two or three transitions, and leg SSP produced one, three or two transitions, respectively (Table 3) (Ndi and Brekke, 1992). Similar to chicken actomyosin (Acton and Dick, 1986) and hen/chicken SSP (Xiong and Brekke, 1990a;Xiong, 1992) at pH 6.0 aggregation transitions in duck leg SSP occurred within a more narrow temperature range (6.6 C) than in breast SSP (13 C).…”
Section: Salt-soluble Proteins (Ssp)mentioning
confidence: 98%
See 1 more Smart Citation
“…No gel formation was observed at less than 48C for all the duck myofibrils studied. A previous study on the aggregation properties of duck breast and leg muscle proteins (Ndi and Brekke 1992) revealed that, depending on muscle type, varying pH from 5.50 to 6.00 results in major changes in protein transition. These changes suggest that pH affects the overall aggregation pattern of the protein extracts by enhancing or suppressing specific constituents of the myosin/actomyosin complex.…”
Section: Resultsmentioning
confidence: 99%
“…Solutions were then heated at 1ЊC/min to 90ЊC. The change in solution turbidity, resulting from aggregate formation, was determined by monitoring optical density at 320 nm (Ndi and Brekke, 1992). First derivative plots were made from the turbidity measurements and used to determine the transition temperature (T max ) of aggregation.…”
Section: Turbidity Measurementsmentioning
confidence: 99%